?PREPARATION OF WEIGHT REDUCING DIET AND ITS BIOLOGICAL AND CLINICAL EVALUATION (Biological Sciences - PJSIR, 1998)
Presentstudieswerecarriedoutforthepreparationofweight reducingdietforobesepeople.Formulationorweightreducing diet isbased on entirely local ingredients. It ischeaper than allother foods imported for this purpose. Clinical evaluation showed thataverage body weightreduction was3 lbsweek']andithadnosideeffectslikehypoglycaemia, hypokalaernia, hyponatraemia andhyperuricaemia.